2009
DOI: 10.1007/s10549-009-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in breast cancer and metastasis

Abstract: The cancer stem cell theory poses that cancers develop from a subset of malignant cells that possess stem cell characteristics and has been proposed to account for the development of a variety of malignancies, including breast cancer. These cancer stem cells (CSC) possess characteristics of both stem cells and cancer cells, in that they have the properties of self-renewal, asymmetric cell division, resistance to apoptosis, independent growth, tumourigenicity and metastatic potential. A CSC origin for breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 166 publications
(215 reference statements)
3
72
0
2
Order By: Relevance
“…With our models and noninvasive imaging, we could monitor early tumor growth and the activities of defined subsets of human breast cancer cells. The relevance of CD44 + CSCs function and clinical outcome has been questioned (17,45,46). This work further supports reports from many other groups that CD44 + cells correlate with EMT, unfavorable prognosis, and metastasis of clinical breast cancer (17,20,21,47).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With our models and noninvasive imaging, we could monitor early tumor growth and the activities of defined subsets of human breast cancer cells. The relevance of CD44 + CSCs function and clinical outcome has been questioned (17,45,46). This work further supports reports from many other groups that CD44 + cells correlate with EMT, unfavorable prognosis, and metastasis of clinical breast cancer (17,20,21,47).…”
Section: Discussionsupporting
confidence: 80%
“…Because CSCs are characterized from various types of cancers, CD44 has been a useful marker for enriching CSCs not only for breast tumors but also a variety of other epithelial tumor models (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). We and others have previously reported that CSCs are more resistant to traditional cancer therapies (4,18,19).…”
mentioning
confidence: 99%
“…Thus, deregulation of EMT-regulating factors in the mammary gland could induce EMT in epithelial mammary cells and/or in stem-like cells, and thus, these cells could later acquire mesenchymal characteristics with invasive and self-renewal capabilities, enabling these cells to develop micrometastasis and macrometastasis in distant organs. These data also support the hypothesis that breast cancer cells may have a stem cell origin (49)(50)(51).…”
Section: Discussionsupporting
confidence: 85%
“…Identification of specific molecular determinants involved in tumour cell homing and colonisation of bone are fundamental for the development of effective therapeutic regimes. During metastatic conversion, breast cancer cells acquire molecular changes enabling invasion of surrounding tissue, vascular spread to distant sites, and proliferation and survival in secondary sites (Lawson Blatch & Edkins 2009, Ding Ellis et al 2010. It is likely that metastasis is a result of a stepwise accumulation of genetic mutations, with different molecular alterations being required for different stages in the metastatic process.…”
Section: Introductionmentioning
confidence: 99%